2013
DOI: 10.3109/01676830.2012.736596
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Transnasal Septotomy for Contralateral Orbital Apex Venous Angioma Resection and Decompression

Abstract: Tumors of the orbital apex region are traditionally difficult to approach surgically due to key anatomic structures found in this highly crowded region. We present a case of progressively enlarging orbital apex venous angioma treated with a novel endoscopic transnasal septotomy technique. We highlight the key steps to this approach, as well as specific landmarks necessary to achieve a safe and successful outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…No systematic reviews or controlled trials were identified in the literature. Thirty‐nine studies contained data for patients who met the inclusion criteria . Of the studies included, 21 were case reports, 8 were case series, and 10 were retrospective chart reviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No systematic reviews or controlled trials were identified in the literature. Thirty‐nine studies contained data for patients who met the inclusion criteria . Of the studies included, 21 were case reports, 8 were case series, and 10 were retrospective chart reviews.…”
Section: Resultsmentioning
confidence: 99%
“…The utility of endoscopic techniques in orbital surgery was first described 3 decades ago, and since then, technological advances have led to an increase in these approaches, most significantly in the past 10 years . Transnasal endoscopic procedures allow direct access to the medial orbital wall and are potentially valuable alternatives in lesions of the inferomedial orbit.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in endoscopic equipment and experience with expanded endonasal approaches (EEA) have expanded their use for lesions at the orbital apex and superior orbital fissure (SOF) 1‐5 . While the optic nerve and the ophthalmic artery travel through the optic canal, other cranial nerves (CN) related to ocular function, including the oculomotor nerve (CN III), trochlear nerve (CN IV), ophthalmic nerve (CN V 1 ), abducens nerve (CN VI), and the superior ophthalmic vein travel through the SOF 6 .…”
Section: Introductionmentioning
confidence: 99%
“…their use for lesions at the orbital apex and superior orbital fissure (SOF). [1][2][3][4][5] While the optic nerve and the ophthalmic artery travel through the optic canal, other cranial nerves (CN) related to ocular function, including the oculomotor nerve (CN III), trochlear nerve (CN IV), ophthalmic nerve (CN V 1 ), abducens nerve (CN VI), and the superior ophthalmic vein travel through the SOF. 6 Tumors or trauma may affect the orbital apex and SOF leading to SOF syndrome or orbital apex syndrome (with vision loss).…”
mentioning
confidence: 99%
“…Transnasal endoscopic approach, through the lamina papyracea exposed with ethmoidectomy and sphenoidectomy, offers a convenient access to the medial and inferior part of the orbit. However, the procedure is technically demanding and, thus, not widespread: the hitherto published clinical material is restricted to case reports only, and very short clinical series focused on tumor biopsies, and decompression in orbital trauma or in endocrine orbitopathy [5][6][7].…”
mentioning
confidence: 99%